Soluble material dissolving property evaluation method for fracturing tool
By measuring the volume change of the cylindrical soluble material specimens in the heated dissolving solution, calculating the dissolution rate and evaluating the expansion rate of the dissolved product, the problems of inaccurate dissolution rate measurement and insufficient evaluation of the dissolved product in the prior art are solved, and the accurate evaluation of the dissolution performance of soluble materials and the reduction of potential clogging risk are achieved.
Patent Information
- Application Number
- CN202311101505.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-29
AI Technical Summary
Existing methods for evaluating dissolution performance of soluble materials lack accurate measurements of dissolution rates and fail to effectively evaluate the potential risk of sanitary products to the wellbore.
The cylindrical soluble material specimens were used to dissolve stably in the heated dissolving solution. By measuring the volume change of the specimen, the dissolution rate was calculated, and the expansion rate of the dissolved product was evaluated to determine the dissolution performance and potential clogging risk.
Accurate evaluation of the dissolution properties of soluble materials is achieved, eliminating the impact of the initial and final rate changes in dissolution, and more accurately assessing the impact of dissolved products on the wellbore and reducing the risk of blockage.
Smart Images

Figure BDA0004420842970000041 
Figure HDA0004420842980000011 
Figure HDA0004420842980000012
Abstract
Description
Technical Field
[0001] The invention relates to a method for evaluating the dissolution performance of soluble materials of fracturing tools such as soluble bridge plugs and soluble ball seats for fracturing in oil and gas fields. Background Art
[0002] In oil and gas field reservoir reconstruction tools, soluble materials are increasingly used. They can not only simplify the tool structure, but also dissolve quickly after fracturing and shorten the production cycle of oil and gas wells. Therefore, the key indicator of soluble materials for manufacturing fracturing tools is solubility. The solubility performance specifically requires the evaluation of the dissolution rate of the soluble material and the risk of the dissolved product blocking the wellbore. The existing evaluation methods for the solubility performance of soluble materials have the following problems: (1) The evaluation method mainly conducts a whole machine dissolution experiment on the tool processed by the soluble material. The evaluation focuses on the time when the tool is completely dissolved, and does not give the solubility performance of the soluble material such as the dissolution rate; (2) The test method for the solubility performance of soluble materials does not consider the influence of the shape of the specimen and the surface oxide layer at the initial stage of dissolution on the dissolution rate. For example, the diameter of a spherical specimen changes continuously during the dissolution process, and the dissolution rate also changes continuously, resulting in the inaccuracy of the test method; (3) After the specimen begins to dissolve, the surface becomes granular, and the accurate dissolution rate cannot be obtained by directly measuring the size of the specimen after dissolution; (4) The dissolved product is not evaluated. For soluble fracturing tools, too much dissolved product may block the wellbore.
[0003] In view of the above problems, it is necessary to establish a more effective method for testing and evaluating the dissolution performance of soluble materials. For example, in Chinese patent CN206832717U, the influence of the processing shape of the soluble material is eliminated by setting a clamp and using a standard cylindrical specimen, and the remaining soluble material of the specimen can be weighed at any time during the dissolution process. However, this patent still has certain problems, including: due to the influence of factors such as the surface oxide layer in the early stage of dissolution and the accumulation of flocculent dissolved products in the later stage, the dissolution rate of the soluble material during the dissolution process is different, making it difficult to accurately evaluate the dissolution performance of the soluble material. Summary of the invention
[0004] The object of the present invention is to provide an accurate, rapid and comprehensive method for evaluating the dissolution performance of soluble materials used in fracturing tools, thereby facilitating the comparison and selection of soluble materials in the processing of fracturing tools.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The method for evaluating the dissolution performance of a soluble material comprises the following steps:
[0007] Step 1: placing a cylindrical soluble material specimen with a volume of V and an end cross-sectional area of S in a heated dissolving solution, and making sure that only the two end surfaces of the cylindrical soluble material specimen are in contact with the heated dissolving solution;
[0008] Step 2: from the time when the cylindrical soluble material sample begins to stably dissolve in the heated dissolving solution, the volume of the dissolved cylindrical soluble material sample is measured at fixed intervals, and then the dissolution time t and the volume of the dissolved cylindrical soluble material sample are recorded;
[0009] Step 3: Draw a stable dissolution curve with the dissolution time t as the horizontal coordinate and the volume of the cylindrical soluble material specimen after dissolution as the vertical coordinate, and then calculate the ratio of K to S. The absolute value of the ratio (K / S) is the dissolution rate of the soluble material, where K is the slope of the stable dissolution curve.
[0010] Preferably, the dissolving liquid is a KCl solution with a mass fraction of 0.2%-0.5%.
[0011] Preferably, the soluble material is selected from one of soluble metals and the like.
[0012] Preferably, the heating temperature of the dissolving solution can be determined according to the specific formation temperature requirement, for example, the heating temperature is 40-60°C.
[0013] Preferably, step 1 specifically includes the following steps: heating the dissolving solution to a specified temperature (e.g., 40-60°C), placing a cylindrical soluble material specimen with a volume of V and an end face cross-sectional area of S into a hollow cylindrical fixture, and then placing the cylindrical soluble material specimen together with the fixture into the dissolving solution (e.g., a KCl solution with a temperature of 40-60°C), thereby using the fixture to ensure that only the end face of the cylindrical soluble material specimen can contact the dissolving solution after being placed in the dissolving solution.
[0014] Preferably, the ratio of the diameter to the length of the cylindrical soluble material specimen is 0.4-0.5, and this ratio can ensure that the cylindrical soluble material specimen approaches or reaches a uniform speed change during the stable dissolution process, thereby improving the accuracy of the dissolution rate measurement.
[0015] Preferably, the step 2 specifically includes the following steps: according to the change of dissolution rate during the complete dissolution of the soluble material, after the cylindrical soluble material specimen (with the clamp) is placed in the dissolving solution (for example, a KCl solution with a temperature of 40-60°C), the dissolved cylindrical soluble material specimen is taken out and weighed according to the set corresponding time intervals (for example, a shorter time interval is used in the dissolution stage where the dissolution rate changes faster at the beginning, and a longer time interval is used in the dissolution stage where the dissolution rate stabilizes and finally slows down), and the residual mass G of the specimen is obtained, and then the dissolution time t when each time interval is reached and the ratio V1 of the residual mass G of the specimen to the density of the soluble material are recorded.
[0016] Preferably, in step 2, the dissolved cylindrical soluble material specimen is dried (eg, oven-dried) before weighing.
[0017] Preferably, in step 3, the stable dissolution curve refers to a line connecting any two points within two dividing points (inflection points) in the dissolution curve drawn according to the dissolution time t recorded in the complete dissolution process and the ratio V1 of the residual mass G of the specimen to the density of the soluble material, so that the slope calculated successively from adjacent points in the dissolution curve no longer changes significantly.
[0018] Preferably, the method for evaluating the dissolution performance of soluble materials also includes the following steps: after a cylindrical soluble material specimen with a volume of V and an end cross-sectional area of S is completely dissolved, measuring the volume V2 of the flocculent dissolved product, and then calculating the ratio of V2 to V, the ratio (V2 / V) being the expansion rate, the flocculent dissolved product being a flocculent precipitate formed by the dissolved product of the soluble material (i.e., a cylindrical soluble material specimen with a volume of V and an end cross-sectional area of S) and the dissolving liquid (e.g., a KCl solution at a temperature of 40-60°C), the larger the volume of the flocculent dissolved product, the less thorough the dissolution (the higher the expansion rate), and the greater the impact on later production (e.g., more prone to blockage), and therefore the smaller the volume of the flocculent dissolved product, the better.
[0019] The beneficial effects of the present invention are embodied in:
[0020] The present invention uses the stable part of the dissolution curve to obtain the straight line slope K, which can eliminate the influence caused by the inconsistent dissolution rate changes of the soluble material in the early and late stages of dissolution, thereby accurately evaluating the dissolution performance of the soluble material after being used to process the fracturing tool.
[0021] Furthermore, the present invention plots the dissolution curve based on the ratio V1 of the residual mass G of the specimen to the density of the soluble material, which can eliminate the influence of the material density and obtain the true volume change of the specimen, which is more accurate than directly measuring the geometric dimensions of the specimen.
[0022] Furthermore, the cylindrical soluble material specimen used in the present invention has a moderate diameter and length ratio, which helps to limit the specimen to dissolve only from the end face. In addition, the dissolving liquid used is a KCl solution with a concentration of 0.2%-0.5%, which can make the soluble material (specifically soluble metals, etc.) in the specimen dissolve at a medium or low speed, thereby ensuring that the dissolution process approaches or reaches a uniform speed change, making the measurement result of the dissolution rate more accurate.
[0023] Furthermore, the present invention helps to improve the calculation speed of the dissolution rate of the soluble material by sequentially calculating the dividing points (inflection points) on the dissolution curve during the complete dissolution process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1The figure is a schematic diagram of the fixture (specimen tooling) structure and clamping of a soluble metal specimen; in the figure: 1. Clamping sleeve; 2. Specimen; 3. Waterproof layer.
[0025] Figure 2 It is the dissolution curve of the soluble metal specimen; in the figure: the dotted line part is the stable dissolution part with a slope of K.
[0026] Figure 3 Schematic diagram of dissolved products; in the figure: the volume of flocculent colloidal precipitation V 2 That is, the volume of flocculent dissolved products, which can be read directly. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The embodiments are only used to explain the present invention, but not to limit the scope of protection of the present invention.
[0028] This embodiment provides a method for evaluating the dissolution performance of a soluble metal (specifically a soluble aluminum alloy) for a fracturing tool, comprising the following steps:
[0029] 1) For oilfield fracturing tools, due to the low formation temperature, a 0.2wt% KCl solution (volume V0, V0 = 2000mL) was heated to 40°C and kept at a constant temperature. A soluble metal specimen 2 (cylinder with a diameter-to-length ratio of 0.4, volume V = 15700mm) with a diameter of 2cm and a length of 5cm was placed on the surface of the fracturing tool. 3 ) is placed in Figure 1 In the fixture shown in the figure, the outer layer of the fixture is a cylindrical clamping sleeve 1, and the inner layer of the fixture is a rubber insulation layer (as a waterproof layer 3) attached to the inner wall of the clamping sleeve 1. The rubber insulation layer is used to tightly wrap the side of the soluble metal specimen 2 placed in the fixture to ensure that only the end surface of the soluble metal specimen 2 can contact the solution.
[0030] 2) At the initial stage of dissolution of the soluble metal specimen 2, take out the specimen and dry it every 0.5 h, measure the residual mass of the specimen, and calculate the ratio of the residual mass of the specimen to the density of the material (soluble metal), that is, the true residual volume V1 of the specimen. Record the corresponding dissolution time and the true residual volume V1 of the specimen. The recorded results are shown in Table 1.
[0031] 3) After 2 hours of dissolution, measure the remaining mass of the specimen every 1-2 hours, and calculate the ratio of the remaining mass to the density of the material (soluble metal). Record the corresponding dissolution time and the actual remaining volume V1 of the specimen until it is completely dissolved. The results are shown in Table 1.
[0032] Table 1. Dissolution time and residual volume of soluble metal specimens
[0033]
[0034] 4) After the soluble metal specimen 2 is completely dissolved, measure the volume V2 of the flocculent dissolved product in the KCl solution, such as Figure 3 As shown, the flocculent dissolved product is a flocculent colloidal mixture of dissolved solid residue and water, so its volume V2> (total volume of the dissolved system-V0), and the calculation of V2 / V, that is, the expansion rate, can be used to determine whether the dissolved product of the soluble fracturing tool will block the wellbore. Generally, when V2 / V>10, there is a risk of blocking the wellbore. This is because the dissolved product will solidify into blocks under high formation temperature. When V2 / V>10, the formation pressure cannot flush the solid block residue in the wellbore, which will cause the wellbore to be blocked. In this example, the V2 / V of the selected material (soluble metal) is 1:6, which is judged to be non-blocking.
[0035] 5) Draw a curve of the relationship between dissolution time and V1, such as Figure 2 As shown, take the stable part of the curve slope (i.e. the straight line segment in the middle of the curve) and calculate the slope K = -1475 mm 3 / h, that is, the volume of the specimen dissolved per hour, and then calculate the absolute value of K / S, and the obtained 1.17mm / h is the dissolution rate of the soluble metal. The dissolution rate is used to characterize the dissolution performance index of the soluble metal, which means the thickness of the soluble metal dissolved per unit time and unit area under the conditions of specified temperature and dissolving solution, and the unit is mm / h.
[0036] Compared with step 3, the time interval used in measuring the residual mass of the specimen in step 2 is shorter. This is because at the initial stage of dissolution, the surface of the soluble metal specimen 2 is relatively smooth and has a thin oxide layer. The dissolution rate at this time cannot reflect the actual dissolution performance. It is necessary to find the inflection point of the dissolution curve, so the measurement time interval is shorter. The sign of the inflection point is: the slope K of the line connecting point N and N-1 (N-1,N) The slope K of the line connecting points N-1 and N-2 (N-2,N-1) Compared with the absolute value of the slope change rate, that is, |[K (N-1,N) -K (N-2,N-1) ] / K (N-2,N-1) ×100%|≤10%, then points N, N-1, and N-2 meet the true dissolution rate conditions. Figure 2 In this example, the first inflection point is the 6th point, the second inflection point is the 8th point, and the slope of the line connecting the 6th and 7th points is K (6,7) -1435mm 3 / h, compared with the slope of the line connecting the first two points (points 5 and 6), the absolute value of the slope change rate is 5%, and the slope of the line connecting the 7th and 8th points is K (7,8) -1514mm 3 / h, compared with the slope of the line connecting the first two points (points 6 and 7), the absolute value of the slope change rate is 8%, so the slope of the line connecting any two points between points 6 and 8 can reflect the actual dissolution performance.
[0037] In this example, the slope K is K (6,7) and K (7,8) Average value - 1475mm 3 / h. But in fact, it can also be K (6,7) As K, this measures dissolution properties more quickly.
Claims
1. A method for evaluating the dissolution performance of a soluble material used in a fracturing tool, characterized in that: The method for evaluating the dissolution performance of a soluble material comprises the following steps: 1) placing a cylindrical soluble material specimen with a volume of V and an end cross-sectional area of S in a heated dissolving solution, and making sure that only the two end surfaces of the cylindrical soluble material specimen are in contact with the heated dissolving solution; 2) starting from the time when the cylindrical soluble material specimen stably dissolves in the heated dissolving solution, measuring the volume of the dissolved cylindrical soluble material specimen at fixed intervals, and then recording the dissolution time t and the volume of the dissolved cylindrical soluble material specimen; 3) A stable dissolution curve is drawn with the dissolution time t as the horizontal coordinate and the volume of the cylindrical soluble material specimen after dissolution as the vertical coordinate, and then the ratio of K to S is calculated. The absolute value of the ratio is the dissolution rate of the soluble material, where K is the slope of the stable dissolution curve.
2. A method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 1, characterized in that: The dissolving liquid is a KCl solution with a mass fraction of 0.2%-0.5%.
3. A method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 1, characterized in that: The soluble material is selected from one of soluble metals.
4. A method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 1, characterized in that: The heating temperature of the dissolving solution is 40-60°C.
5. The method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 1, characterized in that: The step 1 specifically includes the following steps: heating the dissolving solution to a specified temperature, placing a cylindrical soluble material specimen with a volume of V and an end cross-sectional area of S into a hollow cylindrical fixture, and then placing the cylindrical soluble material specimen together with the fixture into the dissolving solution.
6. A method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 1 or 5, characterized in that: The ratio of the diameter to the length of the cylindrical soluble material specimen is 0.4-0.
5.
7. A method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 1, characterized in that: The step 2 specifically includes the following steps: according to the change of dissolution rate during the complete dissolution of the soluble material, after the cylindrical soluble material specimen is placed in the dissolving solution, the dissolved cylindrical soluble material specimen is taken out and weighed at the set corresponding time intervals to obtain the residual mass G of the specimen, and then the dissolution time t when each time interval is reached and the ratio V1 of the residual mass G of the specimen to the density of the soluble material are recorded.
8. A method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 7, characterized in that: In the step 2, the dissolved cylindrical soluble material specimen is dried before weighing.
9. A method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 7, characterized in that: In step 3, the stable dissolution curve refers to a line connecting any two points within two dividing points in the dissolution curve drawn according to the dissolution time t recorded in the complete dissolution process and the ratio V1 of the residual mass G of the specimen to the density of the soluble material, so that the slope calculated successively from adjacent points in the dissolution curve no longer changes significantly.
10. The method for evaluating the dissolution performance of a soluble material for a fracturing tool according to claim 1, characterized in that: The method for evaluating the dissolution performance of soluble materials also includes the following steps: after a cylindrical soluble material specimen with a volume of V and an end cross-sectional area of S is completely dissolved, the volume V2 of the flocculent dissolved product is measured, and then the ratio of V2 to V is calculated, and the ratio is the expansion rate. The flocculent dissolved product is a flocculent precipitate formed by the soluble material dissolved product and the dissolved liquid.
Citation Information
Patent Citations
Device and method for testing rock salt dissolution rates
CN103163043A
Method for predicting remaining life cycle of lithium manganese-lithium titanate battery
CN107271610A
Method for accelerating dissolution rate of soluble bridge plug
CN110656904A
Method for measuring dissolution rate of salt ore
CN115060622A
Soluble material dissolubility can visual evaluation device
CN206832717U